The development and implementation of The LAC Pack in West Lothian - Janet Guild (Scottish Journal of Residential Child Care)
Research has shown that children looked after by the local authority are behind their peers in terms of educational attainment. They are more likely to leave school early without qualifications, and are at risk of school exclusion (HM Inspectors of Schools and the Social Work Services Inspectorate, 2001). This paper will outline the development and implementation of a resource which is designed to address some of these issues.